MAPPING THE FUTURE: A COMPREHENSIVE EXPLORATION OF GLOBAL TRENDS IN SCIENCE BASED TARGET SETTING - Zhang , Yujie; Li, Minghui (Advanced Journal of Environmental Sciences (AJES), 2024)
The Science Based Targets Initiative (SBTi), inaugurated in 2014 by the United Nations Global Compact (UNGC), the Center for Global Environmental Information and Research (CDP), the World Resources Institute (WRI), and the World Wide Fund for Nature (WWF), stands as a crucial international endeavor. Specifically designed to guide companies in establishing climate-focused carbon reduction targets, the SBTi addresses the imperative for businesses to align their practices with global sustainability goals. This paper provides an in-depth exploration of the SBTi, examining its inception, structure, and impact on corporate climate action. By leveraging the collaborative efforts of key global entities, the SBTi offers a standardized framework for companies to set and pursue ambitious carbon reduction targets. These targets, rooted in scientific evidence, contribute to the overarching goals of mitigating climate change and advancing sustainable development. The study delves into the key components of the SBTi methodology, emphasizing its role in fostering accountability, transparency, and tangible progress toward a low-carbon future. As a beacon for corporate climate responsibility, the SBTi has gained momentum globally, with an increasing number of companies committing to align their operations with the initiative's principles. The paper explores case studies and examples of successful SBTi implementation, shedding light on the diverse strategies employed by businesses across different sectors. Additionally, it examines challenges faced by companies in adopting science-based targets and proposes strategies to overcome these hurdles. In essence, this research contributes to the growing body of knowledge on sustainable business practices and climate action. It underscores the significance of the SBTi as a transformative tool for businesses striving to play a meaningful role in combating climate change. By providing a comprehensive understanding of the SBTi and its implications, this study aims to inspire and guide companies towards more impactful and science-driven climate strategies.